Busulfan and thiotepa as a conditioning regimen for autologous stem cell transplantation in patients with multiple myeloma: A study of the Korean Multiple Myeloma Working Party (KMMWP-1801 study) - Song, Ga-Young; Jung, Sung-Hoon; Kim, Jin Seok; Eom, Hyeon Seok; Moon, Joon Ho; Yhim, Ho-Young; Kim, Kihyun; Min, Chang-Ki; Lee, Je-Jung (Frontiers in Oncology, 2022)
Background Autologous stem cell transplantation (ASCT) remains the standard of care for patients with newly diagnosed multiple myeloma (MM). Several attempts to improve the efficacy of conditioning regimen have been conducted in MM, but no more effective regimen than conventional high-dose melphalan has been introduced. Objective In this study, the efficacy and toxicity of busulfan and thiotepa (BuTT) and those of high-dose melphalan (HD-MEL) were compared retrospectively as a conditioning regimen for ASCT in patients with MM. Study design Included in the analysis were 114 patients who received BuTT and 114 patients who received HD-MEL treatment between March 2008 and May 2020. BuTT regimen was consisted of intravenous thiotepa 5 mg/kg once a day from days -7 to -6 followed by intravenous busulfan 3.2 mg/kg once a day from days -5 to -3. HD-MEL conditioning regimen was consisted of melphalan 100 mg/m2 once a day from days -3 to -2. Results The overall response rate after ASCT did not differ between BuTT and HD-MEL (94.7% in BuTT vs. 97.4% in HD-MEL, p = 0.333). After a median follow-up of 47.6 months, progression-free survival (PFS) tended to be longer in the BuTT group (median PFS, 41.5 months vs. 30.3 months; hazard ratio (HR), 0.706; 95% confidence interval (CI), 0.497–1.004, p = 0.053). In the subgroup analysis with patients who did not proceed to maintenance or consolidation treatment after ASCT, the difference in PFS became more significant (median PFS, 41.5 months vs. 24.4 months; HR, 0.621; 95% CI, 0.388–0.993; p = 0.047). In addition, the BuTT group had fewer adverse events such as grade 3 or 4 stomatitis and diarrhea than the HD-MEL group (stomatitis, 10.5% vs. 23.7%, p = 0.013; diarrhea, 10.5% vs. 25.4%, p = 0.005). There was no difference in the occurrence of venous-occlusive disease (2.6% in BuTT vs. 0.9% in HD-MEL, p = 0.622). Conclusion Our study results suggest that BuTT is an effective alternative conditioning regimen with reduced toxicity in patients with newly diagnosed MM.